Process optimization for in-house, lab scale pellet bead production using twin-screw extruder and spheroniser - Csendes, Orsolya; Haimhoffer, Ádám; Révész, Réka; Vasvári, Gábor; Kuralgaliyeva, Adina (De Remediis, 2025)
Multiparticulate dosage forms are becoming more popular than single-unit forms because they offer benefits such as more consistent gastric emptying, a lower chance of dose dumping, and flexible drug release patterns [1]. Among the available production methods, extrusion-spheronization is preferred because it can handle high amounts of active ingredients without creating large particles, and it also allows for the easy combination of multiple drugs in one unit at any ratio [2]. The aim of this research is to determine the optimal parameters of the extruder, namely, the screw rotation speed, liquid addition rate and powder feeding rate, to determine the independent process parameters of the spheroniser, and to measure the loss-on-drying values, particle size distribution, and morphology of extrudates. The required machines to produce pellets are a twin-screw extruder, a spheroniser, a peristaltic pump, and a cooling system. Extrudates were obtained by using a mixture of microcrystalline cellulose, corn starch, lactose monohydrate and 10% povidone solution.